Pseudo-randomness in cryptography - Bansal Arushi (Nanyang Technological University, 2024)
This paper explores the pivotal role of randomness in ensuring the robustness of cryptographic systems. By conducting attacks on historically prevalent Pseudo-Random Number Generators (PRNGs), namely - Dual Elliptic Curve Deterministic Bit Number Generator (Dual-EC-DRBG), Truncated Linear Congruential Generator (LCG), and Mersenne Twister – it demonstrates the causes of inadequate randomness and implications of these significant security vulnerabilities. The analysis reveals how these vulnerabilities can be exploited, undermining the security of their cryptographic applications.